Features of creative project budget formation - Bilous, Oleksandr (Луцьк: Вежа-Друк, 2023)
The complexity of projects in the creative industries requires organizing the work of teams, efficiently allocating resources, and monitoring the implementation of tasks. The competitive environment challenges creative companies to quickly introduce new products and innovations. The challenges of change require adaptability and flexibility in project planning and execution. Considering these aspects, effective project management becomes a key factor for success in the creative industry. One of the key aspects of implementing creative ideas and projects is the formation of a budget that supports these ideas and allows them to be realized. Project cost planning is the most important component of its successful implementation.
Keywords: creative industries; budgeting requirements; project management; 502.333